THE IMPACT OF INTERNET AND SOCIAL MEDIA USE ON PHYSICAL AND MENTAL HEALTH: A REVIEW - Endler, Olga; Czerniewska, Julia; Dutkiewicz, Dominika; Fidelus, Jakub; Filuk, Magdalena; Ciastoń, Marianna; Mądrzak, Julia; Jurkowska, Klaudia; Dybicz, Mikołaj; Handzel, Marta (International Journal of Innovative Technologies in Social Science, 2026)
Background: Internet and social media use have become integral to everyday life and are increasingly discussed as factors that may influence both physical and mental health. Existing literature suggests that their effects are complex and depend on multiple factors, including user characteristics, platform features, emotional involvement, and type of content.Aim: The aim of this narrative review was to examine how internet and social media use affect physical and mental health across different populations and health domains.Methods: This paper was prepared on the basis of a literature review included empirical studies, systematic reviews, meta-analyses, scoping reviews, and qualitative papers. The findings were synthesized narratively and organized into major thematic areas, including mental health, sleep, body image, eating behavior, loneliness, online health-information seeking, and health-related content shared by influencers.Results: The reviewed literature indicates that the effects of internet and social media use are not uniform. The most frequently reported mental health outcomes were depression, anxiety, stress, psychological distress, low self-esteem, fear of missing out, loneliness, body dissatisfaction, and problematic or addictive use. Sleep emerged as one of the most consistently affected physical health domains, with bedtime use, frequent checking, and emotionally intense engagement repeatedly associated with poorer sleep quality and shorter sleep duration. Appearance-focused content was commonly linked to body dissatisfaction, disordered eating, and maladaptive comparison processes, while anxiety-driven online health-information seeking was associated with cyberchondria, hyperdiagnosis, and poor health decisions. At the same time, several studies identified benefits of digital platforms, including communication, self-expression, peer support, health advocacy, and reduced isolation in specific groups.Conclusion: Internet and social media use can both benefit and harm health. Their effects depend more on patterns, meanings, and contexts of use than on exposure alone.